Glucose-based spiro-oxathiazoles as in vivo anti-hyperglycemic agents through glycogen phosphorylase inhibition. Issue 5 (10th January 2020) - Goyard, David; Kónya, Bálint; Czifrák, Katalin; Larini, Paolo; Demontrond, Fanny; Leroy, Jérémy; Balzarin, Sophie; Tournier, Michel; Tousch, Didier; Petit, Pierre; Duret, Cédric; Maurel, Patrick; et al.
Abstract : Spiro-glyco-heterocycles were prepared on a gram scale from a thiolactone obtained by thermolysis of a thiosulfinate. Lowering of glycaemia in diabetic rat models is pointing toward potential new treatment of type 2 diabetes. Abstract : The design of glycogen phosphorylase (GP) inhibitors targeting the catalytic site of the enzyme is a promising strategy for a better control of hyperglycaemia in the context of type 2 diabetes. Glucopyranosylidene-spiro-heterocycles have been demonstrated as potent GP inhibitors, and more specifically spiro-oxathiazoles. A new synthetic route has now been elaborated through 1, 3-dipolar cycloaddition of an aryl nitrile oxide to a glucono-thionolactone affording in one step the spiro-oxathiazole moiety. The thionolactone was obtained from the thermal rearrangement of a thiosulfinate precursor according to Fairbanks' protocols, although with a revisited outcome and also rationalised with DFT calculations. The 2-naphthyl substituted glucose-based spiro-oxathiazole 5h, identified as one of the most potent GP inhibitors ( K i = 160 nM against RMGPb) could be produced on the gram-scale from this strategy. Further evaluation in vitro using rat and human hepatocytes demonstrated that compound 5h is a anti-hyperglycaemic drug candidates performing slightly better than DAB used as a positive control. Investigation in Zucker fa / fa rat model in acute and subchronic assays further confirmed the potency of compound 5h since it lowered blood glucose levels by ∼36% at 30 mg kg −1 and ∼43% at 60 mg kg −1 . The present study is one of the few in vivo investigations for glucose-based GP inhibitors and provides data in animal models for such drug candidates.